Selective Suprascapular and Axillary Nerve Block Provides Adequate Analgesia and Minimal Motor Block. Comparison with Interscalene Block - Patrícia Falcão Pitombo; Rogério Meira Barros; Marcos Almeida Matos; Norma Sueli Pinheiro Módolo (Brazilian Journal of Anesthesiology, 2013)
Background and objective: Shoulder arthroscopic surgeries evolve with intense postoperative pain. Several analgesic techniques have been advocated. The aim of this study was to compare suprascapular and axillary nerve blocks in shoulder arthroscopy using the interscalene approach to brachial plexus blockade. Methods: According to the technique used, sixty-eight patients were allocated into two groups: interscalene group (IG, n = 34) and selective group (SG, n = 34), with neurostimulation approach used for both techniques. After appropriate motor response, IG received 30 mL of 0.33% levobupivacaine in 50% enantiomeric excess with adrenalin 1:200,000. After motor response of suprascapular and axillary nerves, SG received 15 mL of the same substance on each nerve. General anesthesia was then administered. Variables assessed were time to perform the blocks, analgesia, opioid consumption, motor block, cardiovascular stability, patient satisfaction and acceptability. Results: Time for interscalene blockade was signiﬁcantly shorter than for selective blockade. Analgesia was signiﬁcantly higher in the immediate postoperative period in IG and in the late postoperative period in SG. Morphine consumption was signiﬁcantly higher in the ﬁrst hour in SG. Motor block was signiﬁcantly lower in SG. There was no difference between groups regarding cardiocirculatory stability and patient satisfaction and acceptability. Failure occurred in IG (1) and SG (2). Conclusions: Both techniques are safe, effective, and with the same degree of satisfaction and acceptability. The selective blockade of both nerves showed satisfactory analgesia, with the advantage of providing motor block restricted to the shoulder. Keywords: Anesthesia, Conduction, Anesthetics, Local/levobupivacaine, Brachial Plexus, Orthopedic Procedures, Shoulder Joint